Alcohol use in bipolar disorder: A neurobiological model to help predict susceptibility, select treatments and attenuate cortical insult. (September 2015) - Chitty, Kate M.; Lagopoulos, Jim; Hickie, Ian B.; Hermens, Daniel F.
Highlights: We review two neurobiological impairments common to alcohol use and bipolar disorder. We propose that N-methyl-d -aspartate receptor impairments contribute to the risk of alcohol misuse in bipolar disorder. We propose oxidative stress mediates alcohols effect on bipolar disorder neurotrajectory. Abstract: In a series of neurophysiological and neuroimaging studies we investigated the neurobiology related to alcohol use in young people with bipolar disorder. Impairments were identified across frontal and temporal representations of event-related potential and proton magnetic resonance spectroscopy markers; mismatch negativity and in vivo glutathione, respectively. We propose these findings reflect impairments in the N-methyl-d -aspartate receptor and antioxidant capacity. This review seeks to place these findings within the broader literature in the context of two propositions: 1. Pathophysiological impairments in N-methyl-d -aspartate receptor functioning in bipolar disorder contribute to susceptibility toward developing alcohol problems. 2. Alcohol aggravates bipolar disorder neuroprogression via oxidative stress. A neurobiological model that incorporates these propositions is presented, with a focus on the potential for N-methyl-d -aspartate receptor antagonism and glutathione augmentation as potential adjunctive pharmacotherapies to treat the comorbidity. While this review highlights the importance of alcohol monitoring and reduction strategies in the treatment of bipolar disorder, the clinical impact of the proposed model remains limited by the lack of controlled trials of novel pharmacological interventions.